Mental state verbs used by mother–child dyads in Japanese and English: Implications for the development of Theory of Mind. Issue 1 (February 2020) - Suzuki, Takaaki; Nomura, Jun
Mental state terms are believed to be closely related to the development of Theory of Mind (ToM). This study focuses on mental state verbs (MSVs) and investigates how they are used by Japanese-speaking mother–child dyads compared to their English-speaking counterparts. Analyses of their spontaneous speech from the CHILDES archives show that children's production of MSVs is greatly influenced by the mothers' input in both languages and that Japanese MSVs are used less frequently than English MSVs in both the children's and mothers' utterances. In addition, the syntactic properties of MSVs show that complements under MSVs tend to be null in Japanese, whereas those in English are more likely to be overtly expressed. This difference observed in the mothers' input and children's production can be a contributing factor underlying the developmental delay of ToM in Japanese.